2017
DOI: 10.1038/s41598-017-03614-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical Fibronectin Improves Wound Healing of Irradiated Skin

Abstract: Wound healing is significantly delayed in irradiated skin. To better understand global changes in protein expression after radiation, we utilized a reverse phase protein array (RPPA) to identify significant changes in paired samples of normal and irradiated human skin. Of the 210 proteins studied, fibronectin was the most significantly and consistently downregulated in radiation-damaged skin. Using a murine model, we confirmed that radiation leads to decreased fibronectin expression in the skin as well as dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…For instance, human fetus [ [70] , [71] , [72] ] and invertebrate animals newts [ 73 ] heal wounds much faster because their provision matrices contain much more fibronectins that allow cells to migrate and proliferate faster. The topical application of pure soluble fibronectins enhances normal and diabetic wound healing in animals [ 70 , [74] , [75] , [76] , [77] , [78] ]. These soluble fibronectins aggregate or attach to surrounding tissue, but do not form a 3D matrix in the wound bed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, human fetus [ [70] , [71] , [72] ] and invertebrate animals newts [ 73 ] heal wounds much faster because their provision matrices contain much more fibronectins that allow cells to migrate and proliferate faster. The topical application of pure soluble fibronectins enhances normal and diabetic wound healing in animals [ 70 , [74] , [75] , [76] , [77] , [78] ]. These soluble fibronectins aggregate or attach to surrounding tissue, but do not form a 3D matrix in the wound bed.…”
Section: Discussionmentioning
confidence: 99%
“…During normal wound healing, fibronectin can induce the regeneration of epithelial tissue by recognizing the RGD sequence on the epithelial cell integrin receptor α5β1 [32, 33]. However, the absence of fibronectin expression in irradiated skin leads to skin wounds that do not heal properly [34]. It was also reported that fibronectin is regulated by TGF-β1 in a c-Jun N-terminal kinase-dependent and Smad4-independent manner [35].…”
Section: Discussionmentioning
confidence: 99%
“…54 FINC is a glycoprotein involved in many cellular mechanisms such as cell growth and migration, [55][56][57][58][59] and like collagen, contains a number of binding sites for growth factors, including fibroblast growth factor, vascular endothelial growth factor, and platelet-derived growth factor, which have been shown to promote wound healing. [60][61][62] With regard to lipase inhibitor activity, we found more abundance of APOA1 in PU compared with control tissue. APOA1 is the major structural component of high-density lipoproteins (HDL), and has anti-inflammatory and immunomodulatory functions in addition to endothelial protective properties.…”
Section: Discussionmentioning
confidence: 99%